2020
DOI: 10.1139/cjps-2019-0139
|View full text |Cite
|
Sign up to set email alerts
|

Witchweed [Striga hermonthica (Del.) Benth] control using imazapyr seed coating in maize hybrids in the Nigerian savannah

Abstract: Witchweed [Striga hermonthica (Del.) Benth] is a major parasitic weed of most cereal crops in Africa, including maize. Seed treatment with low doses of acetolactate synthase–inhibiting herbicides, such as imazapyr, was introduced in the 1990s to control witchweed. Field trials were conducted in four locations in Nigeria in 2007 and 2008, to assess the effect of coating seeds of several maize hybrids with imazapyr on witchweed control. The hybrids had genes for imidazolinone herbicide resistance (IR), as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…IRM genotypes varieties reduced the number of shoots that had flowered in both locations. This results correlate with other studies [8,22]. Similarly, it has been noted that using herbicide coated seed reduced striga weed density in the farmer's field by 4.9-7.9 compared to when susceptible varieties were used [29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IRM genotypes varieties reduced the number of shoots that had flowered in both locations. This results correlate with other studies [8,22]. Similarly, it has been noted that using herbicide coated seed reduced striga weed density in the farmer's field by 4.9-7.9 compared to when susceptible varieties were used [29].…”
Section: Discussionsupporting
confidence: 90%
“…Stunted growth observed in commercial genotypes used in this study was attributed to early striga parasitism and high weed density that caused maize-weed competition for water, nutrients and light. Additionally, it has also been indicated that using IR coated genotypes reduces the effects of striga weed on maize height [8]. In a study on harmful effects of weeds on maize performance results showed that competition for growth factors by weeds reduces the height of maize and ultimately the yield [36,38].…”
Section: Discussionmentioning
confidence: 99%
“…Cardoso et al (2011), Kabambe et al (2014), and Gwatidzo et al (2020) reported that higher yields were observed on resistant varieties which agreed with the current findings. This indicated that the Alectra reaction had an impact on the amount of yield on IT82E-16 as it was highly susceptible to the parasitic weed and it was not a surprise to observe as susceptible cowpea varieties suffer yield reduction up to 100 % in a field situation (Boukar et al, 2016;CABI, 2017;Chikoye et al, 2020).…”
Section: Roles Of Cowpea Variety On a Vogelii Effectsmentioning
confidence: 99%